2021
DOI: 10.3390/socsci10010009
|View full text |Cite
|
Sign up to set email alerts
|

Do Work–Life Measures Really Matter? The Impact of Flexible Working Hours and Home-Based Teleworking in Preventing Voluntary Employee Exits

Abstract: Numerous studies have demonstrated the importance of work–life measures, which are designed to contribute to job quality and help reconcile employees’ work and personal lives. In our study, we asked whether such measures can also work as inducements to prevent employees from voluntarily leaving a firm. We considered flexible working hours and home-based teleworking as flexibility measures that are potentially attractive to all employees. To address the possible bias caused by sketchy implementation and their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 83 publications
5
41
1
1
Order By: Relevance
“…Teleworking became widespread in the early 1990s as a result of organizations' demand for remote working settings (Di Martino and Wirth 1990;Neirotti et al 2013). Teleworking's efficacy was also boosted by the demand for work-life balance as a result of the growing number of single parents in today's world (Baruch 2000;Marx et al 2021). Bentley et al (2016) responded to the rapid development of ICT and the pandemic crisis and suggested that teleworking should be reintroduced.…”
Section: Introductionmentioning
confidence: 99%
“…Teleworking became widespread in the early 1990s as a result of organizations' demand for remote working settings (Di Martino and Wirth 1990;Neirotti et al 2013). Teleworking's efficacy was also boosted by the demand for work-life balance as a result of the growing number of single parents in today's world (Baruch 2000;Marx et al 2021). Bentley et al (2016) responded to the rapid development of ICT and the pandemic crisis and suggested that teleworking should be reintroduced.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, gender differences in work–family conflicts might be explained by the fact that women have comparably fewer opportunities to engage in flexible work. However, the evidence suggests that flexible work can also be considered a demand, especially if the flexibility options serve the interests of the employer more than those of the employee ( Abendroth and Diewald, 2019 ; Marx et al, 2021 ). Consequently, studies have found positive as well as negative effects on both WFC and FWC ( Allen et al, 2013 ), especially when it comes to working from home ( Allen et al, 2015 ).…”
Section: Gender and Parenthood Differences In Work–family Conflicts During Covid-19mentioning
confidence: 99%
“…This equally needs employee to work in a comfortable environment, have rest and spend appropriate time on working (Kazekami,2020). According to Marx, Mareike and Martin (2021) an imbalance in work and life will result in work-life conflict causing poor performance and burnout, and can caused mental health issues like depression, alcohol consumption and increase in smoking. This implies that work-life balance is not easy of tracking based on setting standard on performance dashboard but employer is expected to give critical attention to how employee is able to balance work commitment with his or her personal activities.…”
Section: Work Life Balancementioning
confidence: 99%